Long Term Follow-Up on Pediatric Cases With Congenital Myasthenic Syndromes—A Retrospective Single Centre Cohort Study - Della Marina, Adela; Wibbeler, Eva; Abicht, Angela; Kölbel, Heike; Lochmüller, Hanns; Roos, Andreas; Schara, Ulrike (Frontiers in Human Neuroscience, 2020)
Introduction: Congenital myasthenic syndromes (CMS) refer to a heterogenic group of neuromuscular transmission disorders. CMS-subtypes are diverse regarding exercise intolerance and muscular weakness, varying from mild symptoms to life-limiting forms with neonatal onset. Long-term follow up studies on disease progression and treatment-response in pediatric patients are rare. Patients and methods: We analyzed retrospective clinical and medication data in a cohort of 32 CMS-patients including the application of a standardized, not yet validated test (CMS-ST) to examine muscular strength and endurance in 21 patients at last follow up. Findings obtained in our cohort were compared with long-term follow-up studies of (adult) CMS-cohorts from the literature by taking the underlying molecular mechanisms into consideration. Outcomes of CMS-ST were compared to results of normal clinical assessment. Results: 32 pediatric patients with defects in eight different CMS-genes were followed by a median time of 12.8 years. 59% of patients manifested with first symptoms as neonates, 35% as infants. While 53% of patients presented a reduced walking distance, 34% were wheelchair bound. Even under adequate therapy with pyridostigmine (PS) and 3,4- diaminopyridine, CHAT-mutations led to progression of muscular weakness partly in combination with persistent respiratory and bulbar symptoms. RAPSN, CHRND and CHRNB1 patients with neonatal manifestation, early respiratory problems and bulbar symptoms showed a good and maintained treatment response. CHAT and CHRNE patients required higher PS dosages, whereas RAPSN patients needed a lower mean dosage at last follow up. Benefits of short-term medication and long-term progression of symptoms were highly dependent on the specific genetic defect. CMS-ST carried out in 17/21 patients, determined affected muscle groups including bulbar and ocular symptoms, some of which were not reported by the patients. Conclusions: Our findings and comparison with the literature- suggest a better treatment-response and less severe progression of symptoms present in patients suffering from mutations in CMS-genes directly associated with receptor deficiency, while patients with defect leading to synaptopathy and presynaptic defects tend to have worse outcomes. Assessment of affected muscular groups and clinical symptoms by CMS-ST may be useful tool for optimal therapeutic management of the patients, especially for future clinical studies.